Thermosetting resin composition

Through the combination of acid metallocene polyolefin and epoxy resin, the problem of poor adhesion of substrates with low dielectric characteristics is solved, and the excellent bonding strength and thermal stability of high-frequency flexible printed circuit boards are achieved.

JP7627164B2Active Publication Date: 2025-02-05SANYO CHEM IND LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021067004
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-19
Filing Date
2021-04-12
Publication Date
2025-02-05
Estimated Expiration
2041-04-12

AI Technical Summary

Technical Problem

The prior art is difficult to achieve good adhesion on low-dielectric substrates such as LCP. At the same time, traditional epoxy resins and acrylate adhesives will damage the dielectric properties of FPC, and high-temperature processing is prone to wrinkles and reduce yield.

Method used

The thermally cured resin composition containing acid metallocene polyolefins and epoxy resins is used to improve adhesion and thermal stability with various resin substrates by controlling the acid valence, molecular weight and stereoregulation of α-olefins.

Benefits of technology

It achieves excellent bonding strength and thermal stability to a variety of resin substrates while maintaining low dielectric characteristics, and is suitable for flexible printed circuit boards in high-frequency areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627164000001
    Figure 0007627164000001
  • Figure 0007627164000002
    Figure 0007627164000002
  • Figure 0007627164000003
    Figure 0007627164000003
Patent Text Reader

Abstract

To provide a thermosetting resin composition that has excellent adhesion, and has excellent heat resistance and electric characteristics.SOLUTION: A thermosetting resin composition (Z) contains an acid-modified polyolefin (X) and an epoxy resin (Y). The acid-modified polyolefin (X) contains a polyolefin (A) and an unsaturated carboxylic acid (B) as constituent materials. The weight ratio between an ethylene and a C3-8 α-olefin, constituent monomers of the polyolefin (A), [ethylene / C3-8 α-olefin], is 2 / 98 to 50 / 50. The unsaturated carboxylic acid (B) is unsaturated monocarboxylic acid, unsaturated polycarboxylic acid, and / or unsaturated polycarboxylic acid anhydride. The acid-modified polyolefin (X) satisfies all of the following requirements (1)-(3). (1) The acid value is 1-100 mgKOH / g. (2) The number average molecular weight (Mn) is 1,000-60,000. (3)The α-olefin moiety has an isotacticity of 1-50%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermosetting resin composition. [Background technology]

[0002] In recent years, as the speed of transmitted signals on printed wiring boards increases, signals are becoming higher in frequency. Accordingly, there is an increasing demand for flexible printed circuit boards (FPCs) with low dielectric properties (low dielectric constant, low dielectric loss tangent) in the high frequency range. In response to this demand, liquid crystal polymers (LCPs), syndiotactic polystyrene (sPS), polyphenylene sulfide (PPS), and other low dielectric properties have been proposed as substrates for flexible printed circuit boards (FPCs) instead of conventional polyimide (PI) and polyethylene terephthalate films. However, because the substrates with low dielectric properties have low polarity, when conventional epoxy-based or acrylic-based adhesives are used, the adhesive strength is weak, making it difficult to manufacture FPC components such as coverlay films and laminates. In addition, epoxy-based and acrylic-based adhesives do not have excellent low dielectric properties and impair the dielectric properties of FPCs. On the other hand, polyolefin resins are known to have low dielectric properties. Therefore, adhesive compositions for FPCs using polyolefin resins have been proposed. For example, Patent Document 1 proposes a modified polyamide adhesive composition into which an olefin skeleton is introduced in order to improve the electrical properties of FPCs. Patent Document 2 also proposes an adhesive and a flexible printed wiring board coverlay using an aromatic olefin oligomer type modifier and an epoxy resin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-284515 A [Patent Document 2] JP 2007-63306 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] However, although the compositions of Patent Documents 1 and 2 are described as having adhesive properties with polyimide, it is difficult to obtain adhesive properties with substrates having low dielectric properties such as LCP. In addition, since they are used as modifiers and the olefin skeleton occupying the adhesive composition is small, the dielectric properties of the adhesive are poor. When using an LCP substrate, there is a method in which the LCP is melted without using an adhesive and laminated with copper foil to produce a two-layer substrate. However, this method has problems such as the need for a high-temperature lamination machine, the tendency to wrinkle during processing, and reduced yield.

[0005] That is, an object of the present invention is to provide a thermosetting resin composition that has good adhesion to both various resin substrates such as polyimide and LCP and metal substrates, and also has excellent heat resistance and electrical properties (low dielectric properties). [Means for solving the problem]

[0006] The present inventors have conducted research to achieve the above object, and have arrived at the present invention. That is, the present invention relates to a thermosetting resin composition (Z) containing an acid-modified polyolefin (X) and an epoxy resin (Y), the acid-modified polyolefin (X) contains polyolefin (A) and unsaturated carboxylic acid (B) as constituent raw materials, the weight ratio of ethylene, which is a constituent monomer of the polyolefin (A), to an α-olefin having 3 to 8 carbon atoms [ethylene / α-olefin having 3 to 8 carbon atoms] is 2 / 98 to 50 / 50, the unsaturated carboxylic acid (B) is an unsaturated monocarboxylic acid, an unsaturated polycarboxylic acid, and / or an unsaturated polycarboxylic anhydride, and the acid-modified polyolefin (X) satisfies all of the following requirements (1) to (3): (1) Acid value is 1 to 100 mg KOH / g (2) Number average molecular weight (Mn) is 1,000 to 60,000 (3) Isotacticity of the α-olefin portion is 1-50% Effect of the Invention

[0007] The thermosetting resin composition (Z) of the present invention has the following effects. (1) Excellent pot life. (2) Excellent adhesive strength. (3) The cured product has excellent heat resistance and electrical properties (low dielectric properties) [dielectric constant, dielectric tangent]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] <Polyolefin (A)> The polyolefin (A) in the present invention contains, as constituent monomers, ethylene and an α-olefin having 3 to 8 carbon atoms. Hereinafter, the "α-olefin having 3 to 8 carbon atoms" may be referred to as "α-olefin". Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. Although one, two or more kinds of α-olefins may be used in combination, one kind is preferred. Of the above α-olefins, propylene is preferred from the viewpoints of adhesive strength of the cured product and industrial applicability.

[0009] The weight ratio of ethylene and α-olefin, which are constituent monomers of the polyolefin (A), [ethylene / α-olefin], is 2 / 98 to 50 / 50, preferably 5 / 95 to 40 / 60, and more preferably 10 / 90 to 30 / 70. If the weight ratio [ethylene / α-olefin] is less than 2 / 98, the adhesive strength is poor, and if it exceeds 50 / 50, the heat resistance is poor. The weight ratio [ethylene / α-olefin] is, for example, 1 It can be calculated using H-MNR (nuclear magnetic resonance spectroscopy). Among the (A) materials, ethylene / propylene copolymers are preferred.

[0010] The polyolefin (A) may contain other monomers as constituent monomers in addition to ethylene and α-olefins. In that case, the weight of the other monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 1% by weight or less, based on the weight of all monomers constituting the polyolefin (A). Examples of the other monomers include 2-butene, isobutene, α-olefins having a carbon number [hereinafter sometimes abbreviated as C] of 9 to 30 (1-decene, 1-dodecene, etc.), and unsaturated monomers having a carbon number of 4 to 30 other than α-olefins (for example, vinyl acetate).

[0011] The number average molecular weight (Mn) of the polyolefin (A) is preferably from 800 to 50,000, more preferably from 1,500 to 40,000, and even more preferably from 2,000 to 30,000, from the viewpoints of adhesive strength and solvent solubility.

[0012] In the present invention, the Mn of the polyolefin (A) can be measured by GPC (gel permeation chromatography). In the present invention, the conditions for measuring Mn by GPC are as follows. Apparatus: High temperature gel permeation chromatograph ["AllianceGPCV2000", Waters, Inc.] Detector: Refractive index detector Solvent: orthodichlorobenzene Reference material: polystyrene Sample concentration: 3mg / ml Column stationary phase: PLgel 10 μm, MIXED-B 2 columns in series [Polymer Laboratories, Inc.] Column temperature: 135℃

[0013] The number of double bonds per 1,000 carbon atoms in the polyolefin (A) [the number of carbon-carbon double bonds at the molecular terminals and / or in the molecular chain of the polyolefin (A)] is preferably 0.5 to 20, more preferably 1.0 to 18, and even more preferably 1.5 to 15, from the viewpoints of reactivity with the unsaturated carboxylic acid (B) described below and productivity. Here, the number of double bonds is 1 It can be obtained from the H-NMR spectrum. That is, the peaks in the spectrum are assigned, and the relative value between the number of double bonds in polyolefin (A) and the number of carbon atoms in polyolefin (A) is obtained from the integral value derived from the double bonds at 4.5 to 6 ppm of polyolefin (A) and the integral value derived from polyolefin (A), and the number of double bonds in the molecular terminal and / or molecular chain per 1,000 carbons of polyolefin (A) is calculated. The number of double bonds in the examples described later was determined according to this method.

[0014] The isotacticity of the α-olefin portion of the polyolefin (A) is preferably from 1 to 50%, more preferably from 5 to 45%, and further preferably from 10 to 40%, from the viewpoints of adhesive strength and solvent solubility. The isotacticity of the α-olefin portion of the polyolefin (A) tends to be directly reflected in the isotacticity of the α-olefin portion of the acid-modified polyolefin (X) described below.

[0015] The above isotacticity is 13It can be calculated using C-NMR (nuclear magnetic resonance spectroscopy). In general, when the α-olefin is propylene, the side chain methyl group, and when the α-olefin is 1-butene, 1-pentene, 1-hexene, 1-heptene, or 1-octene, the side chain methylene group next to the main chain methine group are affected by the stereoconfiguration (meso or racemo) of both adjacent (triad), both adjacent (pentad) of the triad, and even both adjacent (septad) of the pentad, and are known to have peaks observed at different chemical shifts. Therefore, the evaluation of stereoregularity is generally performed for the pentad, and the isotacticity in the present invention is also calculated based on the evaluation of the pentad.

[0016] That is, when the α-olefin is propylene, 13 Regarding the carbon peaks derived from the side chain methyl groups in propylene obtained by C-NMR, when the α-olefin is 1-butene, 1-pentene, 1-hexene, 1-heptene, or 1-octene, 13 Regarding the carbon peaks derived from the side chain methylene groups adjacent to the main chain methine groups in the α-olefins obtained by C-NMR, the pentad peak intensity of the α-olefin part of polyolefin (A) is (H), and the pentad peak intensity of the isotactic polyolefin formed only of mesostructure is methyl group when the α-olefin is propylene, and α-olefin is 1-butene, 1-pentene, 1-hexene, 1-heptene, or 1-octene when the α-olefin is 1-octene. 13 When the peak intensity derived from a side-chain methylene group adjacent to a main-chain methine group in an α-olefin obtained by C-NMR is taken as (Ha), the isotacticity is calculated by the following formula: Isotacticity (%) = [(Ha) / Σ(H)] × 100 (1)

[0017] The conditions for measuring the isotacticity in the present invention are as follows. Equipment: JEOL Ltd. ECZ400R Measurement mode: Proton decoupling method Pulse width: 8μsec Pulse repetition time: 4.6sec Relaxation time: 3.0sec Accumulation count: 10,000 times Solvent: orthodichlorobenzene Reference material: Tetramethylsilane Sample concentration: 10mg / mL ·Measurement temperature: 120℃

[0018] The polyolefin (A) in the present invention can be produced, for example, by thermally degrading a high molecular weight polyolefin (A0) (preferably having an Mn of 60,000 to 400,000, more preferably having an Mn of 80,000 to 250,000).

[0019] The thermal degradation method includes a method of heating the high molecular weight polyolefin (A0) (1) in the absence of an organic peroxide, for example, at 300 to 450°C for 0.5 to 10 hours, and (2) in the presence of an organic peroxide [for example, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane], usually at 180 to 300°C for 0.5 to 10 hours. Of these, from the industrial viewpoint and from the viewpoint of the modifying properties of the thermosetting resin composition (X), the method (1) is preferred, which can easily give a product having a larger number of double bonds at the molecular terminals and / or in the molecular chain.

[0020] The weight ratio [ethylene / α-olefin] of the monomers constituting the polyolefin (A) to ethylene and α-olefin tends to be maintained the same as the weight ratio [ethylene / α-olefin] of these monomers in the high molecular weight polyolefin (A0). In addition, the higher the thermal degradation temperature or the longer the thermal degradation time, the greater the number of double bonds per 1,000 carbon atoms tends to be. Furthermore, the smaller the Mn of the high molecular weight polyolefin (A0), the higher the thermal degradation temperature, or the longer the thermal degradation time, the smaller the Mn of the polyolefin (A) tends to be. Furthermore, the higher the isotacticity of the high molecular weight polyolefin (A0), the higher the isotacticity of the polyolefin (A) tends to be. The polyolefin (A) may be used alone or in combination of two or more kinds.

[0021] <Unsaturated Carboxylic Acid (B)> The unsaturated carboxylic acid (B) in the present invention is an unsaturated monocarboxylic acid, an unsaturated polycarboxylic acid and / or an unsaturated polycarboxylic acid anhydride. The unsaturated carboxylic acid (B) is preferably a C3-24 monocarboxylic acid having one polymerizable unsaturated group, a C4-24 polycarboxylic acid having one polymerizable unsaturated group, and / or a C4-24 polycarboxylic anhydride having one polymerizable unsaturated group. Among the unsaturated carboxylic acids (B), examples of the unsaturated monocarboxylic acids include aliphatic monocarboxylic acids (C3-24, e.g., acrylic acid, methacrylic acid, α-ethylacrylic acid, crotonic acid, isocrotonic acid), alicyclic monocarboxylic acids (C6-24, e.g., cyclohexene carboxylic acid); examples of the unsaturated poly(2-3 or more) carboxylic acids or their anhydrides include unsaturated dicarboxylic acids or their anhydrides [aliphatic dicarboxylic acids or their anhydrides (C4-24, e.g., maleic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, and their anhydrides), alicyclic dicarboxylic acids or their anhydrides (C8-24, e.g., cyclohexene dicarboxylic acid, cycloheptene dicarboxylic acid, bicycloheptene dicarboxylic acid, methyltetrahydrophthalic acid, and their anhydrides)], etc. The unsaturated carboxylic acids (B) may be used alone or in combination of two or more. Among the above unsaturated carboxylic acids (B), from the viewpoints of reactivity with the polyolefin (A) and the resin properties of the thermosetting resin composition (Z) described below, unsaturated dicarboxylic acid anhydrides are preferred, and maleic anhydride is more preferred.

[0022] <Acid-modified polyolefin (X)> The acid-modified polyolefin (X) in the present invention contains the above polyolefin (A) and unsaturated carboxylic acid (B) as constituent raw materials. The weight ratio of the polyolefin (A) to the unsaturated carboxylic acid (B) in the acid-modified polyolefin (X) [polyolefin (A) / unsaturated carboxylic acid (B)] is preferably 80 / 20 to 99.5 / 0.5, more preferably 90 / 10 to 99 / 1, from the viewpoints of the resin properties and adhesive strength of the cured product.

[0023] Preferably, the acid-modified polyolefin (X) is obtained by reacting the above-mentioned polyolefin (A) with an unsaturated carboxylic acid (B) in the absence or presence of a radical initiator (C). The acid-modified polyolefin (X) can be more preferably produced by reacting the polyolefin (A) and the unsaturated carboxylic acid (B) with, if necessary, a suitable organic solvent [for example, C3-18 hydrocarbons (hexane, heptane, octane, dodecane, benzene, toluene, xylene, etc.), C3-18 halogenated hydrocarbons (di-, tri-, or tetrachloroethane, dichlorobutane, etc.), C3-18 ketones (acetone, methyl ethyl ketone, di-t-butyl ketone, etc.), C3-18 ethers (ethyl-n-propyl ether, di-n-butyl ether, di-t-butyl ether, dioxane, etc.)] in the presence of a radical initiator (C).

[0024] The radical initiator (C) may be a known one, for example, an azo initiator (azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile, etc.) or a peroxide initiator (dicumyl peroxide, etc.). Of the above radical initiators (C), peroxide initiators are preferred.

[0025] The reaction temperature is preferably 100 to 270°C, more preferably 120 to 250°C, and further preferably 130 to 240°C, from the viewpoints of the reactivity of the polyolefin (A) and the unsaturated carboxylic acid (B) and productivity.

[0026] The acid-modified polyolefin (X) satisfies all of the following requirements (1) to (3). (1) Acid value is 1 to 100 mg KOH / g (2) Number average molecular weight (Mn) is 1,000 to 60,000 (3) Isotacticity of the α-olefin portion is 1-50%

[0027] Requirement (1): The acid value of the acid-modified polyolefin (X) is 1 to 100 mgKOH / g (hereinafter, only numerical values ​​are shown), preferably 3 to 75, and more preferably 5 to 50. The acid value here is a value measured in accordance with JIS K 0070. If the acid value is less than 1, the resin properties of the thermosetting resin composition (Z) are inferior, and if it exceeds 100, the productivity of the acid-modified polyolefin (X) is inferior. The acid value can be appropriately adjusted by the number of double bonds in the polyolefin (A), the weight of the polyolefin (A), and the type and weight of the unsaturated carboxylic acid (B).

[0028] Requirement (2): The Mn of the acid-modified polyolefin (X) is 1,000 to 60,000, preferably 2,000 to 50,000, and more preferably 3,000 to 40,000. If the Mn is less than 1,000, the adhesive strength is poor, and if it exceeds 60,000, the resin properties of the thermosetting resin composition (Z) are poor. The Mn of the acid-modified polyolefin (X) can be measured by GPC in the same manner as the Mn of the polyolefin (A) described above. Furthermore, the Mn of the acid-modified polyolefin (X) can be appropriately adjusted by controlling the Mn of the polyolefin (A), the type and amount of the unsaturated carboxylic acid (B), and the reaction between the polyolefin (A) and the unsaturated carboxylic acid (B).

[0029] Requirement (3): The isotacticity of the α-olefin portion of the acid-modified polyolefin (X) is 1 to 50%, preferably 5 to 45%, and more preferably 10 to 40%. If the isotacticity is less than 1%, the adhesive strength is poor, and if it exceeds 50%, the compatibility with the epoxy resin is poor and the pot life is shortened. Furthermore, the isotacticity of the α-olefin portion of the acid-modified polyolefin (X) can be appropriately adjusted by the isotacticity of the polyolefin (A) and the high molecular weight polyolefin (A0), as described above.

[0030] <Epoxy resin (Y)> The epoxy resin (Y) in the present invention has two or more glycidyl groups in the molecule. As (Y), for example, at least one selected from the group consisting of biphenyl type epoxy resin, naphthalene type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin, tetraglycidyldiaminodiphenylmethane, triglycidyl paraaminophenol, tetraglycidylbisaminomethylcyclohexanone, and N,N,N',N'-tetraglycidyl-m-xylylenediamine can be used. Of the above (Y), preferred are bisphenol A type epoxy resins, novolac type epoxy resins, and dicyclopentadiene type epoxy resins.

[0031] If necessary, a reactive diluent (F16) [e.g., monoepoxide such as 2-ethylhexyl glycyl ether] may be used in combination with (Y). In this case, the amount of (F16) is preferably 1 to 10 parts by weight per 100 parts by weight of (Y).

[0032] <Thermosetting resin composition (Z)> The thermosetting resin composition (Z) of the present invention is a composition containing the above-mentioned acid-modified polyolefin (X) and epoxy resin (Y).

[0033] The content of the epoxy resin (Y) is preferably 5 to 1000 parts by weight, more preferably 5 to 500 parts by weight, and particularly preferably 5 to 200 parts by weight, per 100 parts by weight of the acid-modified polyolefin (X) from the viewpoints of adhesive strength, heat resistance, pot life, and electrical properties.

[0034] The thermosetting resin composition (Z) of the present invention contains the components (X) and (Y), and thus has excellent electrical properties (low dielectric properties) after curing, and can exhibit high adhesion between a low-polarity resin substrate such as LCP and a metal substrate. Also, the thermosetting resin composition (Z) contains the components (X) and (Y), and thus has excellent electrical properties after curing, and can exhibit high solder heat resistance between a low-polarity resin substrate such as LCP and a metal substrate. Furthermore, by containing the components (X) and (Y), it is possible to exhibit all of the following after curing: excellent adhesion between a low-polarity resin substrate such as an LCP and a metal substrate, solder heat resistance, and electrical properties (low dielectric properties). That is, the thermosetting resin composition is applied to a substrate, and the adhesive coating film (adhesive layer) after curing exhibits excellent low dielectric properties.

[0035] <Organic solvent (P)> The thermosetting resin composition (Z) of the present invention may further contain an organic solvent (P). The organic solvent (P) used in the present invention is not particularly limited as long as it dissolves the acid-modified polyolefin (X) and the epoxy resin (Y). Specific examples of such solvents include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, and decane; alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, and ethylcyclohexane; halogenated hydrocarbons such as trichloroethylene, dichloroethylene, chlorobenzene, and chloroform; alcohol solvents such as methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, propanediol, and phenol; acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclohexanone, isophorone, and acetophenone. ketone-based solvents, cellosolves such as methyl cellosolve and ethyl cellosolve, ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and butyl formate, and glycol ether-based solvents such as ethylene glycol mono-n-butyl ether, ethylene glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol mono-n-butyl ether, and tetraethylene glycol mono-n-butyl ether, and these can be used alone or in combination of two or more. Among the above (P), ketone solvents are preferred.

[0036] The amount of the organic solvent (P) is preferably 10 to 1000 parts by weight, more preferably 50 to 800 parts by weight, and particularly preferably 100 to 500 parts by weight, per 100 parts by weight of the acid-modified polyolefin (X) from the viewpoints of pot life and industrial efficiency.

[0037] In addition to the above-mentioned (X), (Y), and (P), the thermosetting resin composition (Z) of the present invention may further contain various additives (F) as necessary within a range that does not impair the effects of the present invention. The additive (F) may be one or more selected from the group consisting of flame retardants (F1), tackifiers (F2), fillers (F3), silane coupling agents (F4), colorants (F5), bulking agents (F6), lubricants (F7), antistatic agents (F8), dispersants (F9), antioxidants (F10), release agents (F11), antibacterial agents (F12), compatibilizers (F13), ultraviolet absorbers (F14) and curing accelerators (F15).

[0038] The thermosetting resin composition (Z) of the present invention may contain a flame retardant (F1) as necessary. Examples of the flame retardant include bromine-based, phosphorus-based, nitrogen-based, and metal hydroxide compounds. Among them, phosphorus-based flame retardants are preferred, and known phosphorus-based flame retardants such as phosphoric acid esters, e.g., trimethyl phosphate, triphenyl phosphate, tricresyl phosphate, and the like, phosphates, e.g., aluminum phosphinate, and phosphazenes, can be used.

[0039] The thermosetting resin composition (Z) of the present invention may contain a tackifier (F2) as needed. Examples of the tackifier include polyterpene resins, rosin resins, aliphatic petroleum resins, alicyclic petroleum resins, copolymer petroleum resins, styrene resins, and hydrogenated petroleum resins.

[0040] The thermosetting resin composition (Z) of the present invention may contain a filler (F3) such as silica, if necessary. The incorporation of silica is highly preferable because it improves heat resistance. Generally, hydrophobic silica and hydrophilic silica are known as silica, but in this case, hydrophobic silica treated with dimethyldichlorosilane, hexamethyldisilazane, octylsilane, etc. is better in terms of imparting moisture absorption resistance.

[0041] The thermosetting resin composition (Z) of the present invention may contain a silane coupling agent (F4) as necessary. The incorporation of a silane coupling agent is highly preferable because it improves adhesion to metals and heat resistance. The silane coupling agent is not particularly limited, but examples thereof include those having an unsaturated group, those having a glycidyl group, and those having an amino group. Among these, silane coupling agents having a glycidyl group, such as γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, are more preferable from the viewpoint of heat resistance.

[0042] The thermosetting resin composition (Z) of the present invention may contain a colorant (F5) as necessary. Examples of the colorant include inorganic pigments (white pigments, cobalt compounds, iron compounds, sulfides, etc.), organic pigments (azo pigments, polycyclic pigments, etc.), and dyes (azo-based, indigoid-based, sulfide-based, alizarin-based, acridine-based, thiazole-based, nitro-based, aniline-based, etc.).

[0043] The thermosetting resin composition (Z) of the present invention may contain a filler (F6) as needed. Examples of the filler include inorganic fillers (calcium carbonate, talc, clay, etc.) and organic fillers (urea, calcium stearate, etc.).

[0044] The thermosetting resin composition (Z) of the present invention may contain a lubricant (F7) as needed. Examples of the lubricant include calcium stearate, butyl stearate, oleic acid amide, polyolefin wax, and paraffin wax.

[0045] The thermosetting resin composition (Z) of the present invention may contain an antistatic agent (F8) as needed. Examples of the antistatic agent include nonionic, cationic, anionic or amphoteric surfactants as described below and in U.S. Patent Nos. 3,929,678 and 4,331,447.

[0046] (1) Nonionic surfactants Alkylene oxide (AO) adduct type nonionics, for example, (poly)oxyalkylene derivatives (AO adducts and higher fatty acid mono- or diesters of polyalkylene glycols) of active hydrogen atom-containing compounds having hydrophobic groups (C8-24 or more) [saturated and unsaturated higher alcohols (C8-18), higher aliphatic amines (C8-24) and higher fatty acids (C8-24), etc.]; (poly)oxyalkylene derivatives of higher fatty acid (C8-24) esters of polyhydric alcohols (C3-60) (Tween type nonionics, etc.); (poly)oxyalkylene derivatives of (alkanol)amides of higher fatty acids (above); poly (poly)oxyalkylene derivatives of polyhydric alcohol (above) alkyl (C3-60) ethers; polyoxypropylene polyols [polyoxypropylene derivatives of polyhydric alcohols and polyamines (C2-10) (Pluronic (registered trademark) type and Tetronic type nonionics)]; polyhydric alcohol (above) type nonionics (for example, fatty acid esters of polyhydric alcohols, polyhydric alcohol alkyl (C3-60) ethers and fatty acid alkanolamides); and amine oxide type nonionics [for example, (hydroxy)alkyl (C10-18) di(hydroxy)alkyl (C1-3) amine oxides].

[0047] (2) Cationic surfactants Quaternary ammonium salt type cationics [tetraalkylammonium salts (C11-100), alkyl (C8-18) trimethylammonium salts and dialkyl (C8-18) dimethylammonium salts, etc.]; trialkylbenzylammonium salts (C17-80) (lauryl dimethylbenzylammonium salts, etc.); alkyl (C8-60) pyridinium salts (cetyl pyridinium salts, etc.); (poly)oxyalkylene (C2-4) trialkylammonium salts (C12-100) (polyoxyethylene lauryl dimethylammonium salts, etc.); and acyl (C8-18) aminoalkyl (C2-4) or acyl (C8-18) oxyalkyl (C2-4) tri[(hydroxy)alkyl (C1-4)] ammonium. salts (sapamine-type quaternary ammonium salts) [these salts include, for example, halides (chlorides, bromides, etc.), alkyl sulfates (methosulfates, etc.) and salts of organic acids (C2-22)]; and amine salt-type cationics: inorganic acid (hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc.) salts and organic acid (above) salts of primary to tertiary amines [for example, higher aliphatic amines (C12-60), polyoxyalkylene derivatives (EO [ethylene oxide] adducts, etc.) of aliphatic amines (methylamine, diethylamine, etc.), and acylaminoalkyl or acyloxyalkyl (above) di(hydroxy)alkyl (above) amines (stearoyloxyethyl dihydroxyethylamine, stearamidoethyl diethylamine, etc.)].

[0048] (3) Anionic surfactants Salts of higher fatty acids (mentioned above) (sodium laurate, etc.), ether carboxylic acids [carboxymethylated products of EO (1-10 mol) adducts, etc.] and their salts; sulfate salts (alkyl and alkyl ether sulfates, etc.), sulfated oils, sulfated fatty acid esters, and sulfated olefins; sulfonates [alkylbenzenesulfonates, alkylnaphthalenesulfonates, dialkyl sulfosuccinates, α-olefin (C12-18) sulfonates, N-acyl-N-methyltaurines (Igepone T type, etc.)]; and phosphate salts (alkyl, alkyl ether, and alkylphenyl ether phosphates, etc.).

[0049] (4) Amphoteric surfactants: Carboxylic acid (salt) type amphoterix [amino acid type amphoterix (laurylaminopropionic acid (salt) etc.) and betaine type amphoterix (alkyl dimethyl betaine and alkyl dihydroxyethyl betaine etc.)]; sulfate ester (salt) type amphoterix [laurylamine sulfate ester (salt), hydroxyethyl imidazoline sulfate ester (salt), etc.]; sulfonic acid (salt) type amphoterix [pentadecylsulfotaurine and imidazoline sulfonic acid (salt), etc.]; and phosphate ester (salt) type amphoterix, etc. [glycerol laurate phosphate ester (salt), etc.].

[0050] Salts of the above anionic and amphoteric surfactants include metal salts, such as alkali metal (lithium, sodium, potassium, etc.), alkaline earth metal (calcium, magnesium, etc.) and Group IIB metal (zinc, etc.) salts; ammonium salts; and amine salts and quaternary ammonium salts.

[0051] The thermosetting resin composition (Z) of the present invention may contain a dispersant (F9) if necessary. Examples of the dispersant include polymers having Mn of 1,000 to 20,000, such as vinyl resins, and vinyl resins other than the polyolefin (A) mentioned above, such as polyvinyl halides (polyvinyl chloride and polyvinyl bromide, etc.), polyvinyl acetate, polyvinyl alcohol, polymethyl vinyl ether, poly(meth)acrylic acid, poly(meth)acrylic acid esters (polymethyl (meth)acrylate, etc.), and styrene resins (polystyrene, acrylonitrile / styrene (AS) resin, etc.); polyester resins (polyethylene terephthalate, etc.), polyamide resins (6,6-nylon and 12-nylon, etc.), polyether resins (polyethersulfone, etc.), polycarbonate resins (polycondensates of bisphenol A and phosgene, etc.), and block copolymers thereof.

[0052] The thermosetting resin composition (Z) of the present invention may contain an antioxidant (F10) if necessary. Examples of the antioxidant include phenol compounds (monocyclic phenols (e.g., 2,6-di-t-butyl-p-cresol), bisphenols (e.g., 2,2'-methylenebis(4-methyl-6-t-butylphenol)), polycyclic phenols (e.g., 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene), sulfur compounds (e.g., dilauryl 3,3'-thiodipropionate), phosphorus compounds (e.g., triphenyl phosphite), and amine compounds (e.g., octylated diphenylamine).

[0053] The thermosetting resin composition (Z) of the present invention may contain a release agent (F11) if necessary. Examples of the release agent include lower (C1-4) alcohol esters of fatty acids (C8-24) (butyl stearate, etc.), polyhydric (dihydric to tetrahydric or higher) alcohol esters of fatty acids (C2-24) (hydrogenated castor oil, etc.), glycol (C2-8) esters of fatty acids (C2-24) (ethylene glycol monostearate, etc.), and liquid paraffin.

[0054] The thermosetting resin composition (Z) of the present invention may contain an antibacterial agent (F12) if necessary. Examples of the antibacterial agent include benzoic acid, sorbic acid, halogenated phenols, organic iodine, nitriles (e.g., 2,4,5,6-tetrachloroisophthalonitrile), thiocyano (methylenebisthiocyanate), N-haloalkylthioimide, copper agents (e.g., 8-oxyquinoline copper), benzimidazole, benzothiazole, trihaloallyl, triazole, organic nitrogen sulfur compounds (e.g., Slaof 39), quaternary ammonium compounds, and pyridine compounds.

[0055] The thermosetting resin composition (Z) of the present invention may contain a compatibilizer (F13) as required. Examples of the compatibilizer include modified vinyl polymers having at least one functional group (polar group) selected from the group consisting of amino groups, hydroxyl groups, and polyoxyalkylene groups, such as the polymers described in JP-A-3-258850, modified vinyl polymers having sulfonic acid groups described in JP-A-6-345927, and block polymers having a polyolefin portion and an aromatic vinyl polymer portion.

[0056] The thermosetting resin composition (Z) of the present invention may contain an ultraviolet absorber (F14) as necessary. Examples of ultraviolet absorbers include benzotriazoles (e.g., 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, benzophenones (e.g., 2-hydroxy-4-methoxybenzophenone), salicylates (e.g., phenyl salicylate), and acrylates (e.g., 2-ethylhexyl-2-cyano-3,3-diphenylacrylate).

[0057] The thermosetting resin composition (Z) of the present invention may contain a curing accelerator (F15) as necessary. Examples of the curing accelerator include aliphatic polyamines, aromatic polyamines, secondary amines, tertiary amines, acid anhydrides, imidazole derivatives, organic acid hydrazides, dicyandiamide and its derivatives, and urea derivatives.

[0058] The total content of the additives (F) is, for example, preferably 300% by weight or less based on the total weight of the (X) and (Y), and from the viewpoint of the functional expression of each additive (F) and from the industrial viewpoint, is more preferably 0.05 to 250% by weight, and further preferably 0.1 to 200% by weight. The amount of each additive used based on the total weight of (X) and (Y) is as follows: (F1) is, for example, 200% by weight or less, preferably 10 to 150% by weight; (F2) is, for example, 50% by weight or less, preferably 10 to 40% by weight; (F3) is, for example, 50% by weight or less, preferably 10 to 30% by weight; (F4) is, for example, 30% by weight or less, preferably 10 to 20% by weight; (F5) is, for example, 5% by weight or less, preferably 0.1 to 3% by weight; (F6) is, for example, 5% by weight or less, preferably 0.1 to 1% by weight; (F7) is, for example, 8% by weight or less, preferably 1 to 5% by weight; (F8) is, for example, (F9) is, for example, 1% by weight or less, preferably 0.1 to 0.5% by weight; (F10) is, for example, 2% by weight or less, preferably 0.05 to 0.5% by weight; (F11) is, for example, 5% by weight or less, preferably 0.01 to 3% by weight; (F12) is, for example, 25% by weight or less, preferably 0.5 to 20% by weight; (F13) is, for example, 15% by weight or less, preferably 0.5 to 10% by weight; (F14) is, for example, 2% by weight or less, preferably 0.05 to 0.5% by weight; (F15) is, for example, 2% by weight or less, preferably 0.05 to 0.5% by weight.

[0059] When the compounds in (F1) to (F15) overlap, each compound should not be used in the amount necessary to achieve the corresponding additive effect, but should be adjusted according to the purpose of use, taking into consideration that the effects of other additives can also be obtained at the same time.

[0060] <Laminate> The thermosetting resin composition (Z) of the present invention can be used for various applications, but is preferably used for adhesion, and more preferably for adhesion between a resin substrate and a resin substrate or between a metal substrate. The laminate of the present invention is a laminate of the thermosetting resin composition (Z) on a substrate (a two-layer laminate of substrate / adhesive layer), or a three-layer laminate of substrate / adhesive layer / substrate. Here, the adhesive layer refers to a layer of the adhesive composition after the thermosetting resin composition (Z) of the present invention is applied to a substrate and dried. The laminate of the present invention can be obtained by applying the thermosetting resin composition (Z) of the present invention to various substrates and drying it according to a conventional method, and further laminating another substrate.

[0061] <Base material> In the present invention, the substrate is not particularly limited as long as it is possible to form an adhesive layer by applying and drying the thermosetting resin composition (Z) of the present invention. Examples of the substrate include resin substrates such as film-like resins, metal substrates such as metal plates and metal foils, and papers.

[0062] Examples of the resin substrate include polyester resin, polyamide resin, polyimide resin, polyamideimide resin, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resin, and fluorine resin. A film-like resin (hereinafter also referred to as a substrate film layer) is preferable.

[0063] As the metal substrate, any conventionally known conductive material that can be used for a circuit board can be used. Examples of materials include various metals such as SUS, copper, aluminum, iron, steel, zinc, and nickel, as well as their alloys, plated products, and metals treated with other metals such as zinc and chromium compounds. Metal foil is preferred, and copper foil is more preferred. The thickness of the metal foil is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 10 μm or more. It is also preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. If the thickness is too thin, it may be difficult to obtain sufficient electrical performance of the circuit, and on the other hand, if the thickness is too thick, the processing efficiency during circuit production may decrease. The metal foil is provided, for example, in a roll form. The shape of the metal foil used in manufacturing the printed wiring board of the present invention is not particularly limited. When using a ribbon-shaped metal foil, its length is not particularly limited. Its width is also not particularly limited, but is preferably about 250 to 500 cm.

[0064] Examples of the paper include fine paper, craft paper, roll paper, glassine paper, etc. Examples of the composite material include glass epoxy, etc.

[0065] Of the above-mentioned substrates, in terms of adhesion to the adhesive composition and durability, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resin, fluorine-based resin, SUS steel plate, copper foil, aluminum foil, and glass epoxy are preferred.

[0066] <Adhesive sheet> The adhesive sheet of the present invention is an adhesive sheet having the laminate. That is, the adhesive sheet is obtained by laminating the laminate and a release substrate via a thermosetting resin composition (Z) [preferably a cured product of (Z)]. Specific configurations include laminate / adhesive layer / release substrate, or release substrate / adhesive layer / laminate / adhesive layer / release substrate. By laminating the release substrate, it functions as a protective layer for the substrate. In addition, by using a release substrate, the release substrate can be released from the adhesive sheet and the adhesive layer can be transferred to another substrate.

[0067] The adhesive sheet of the present invention can be obtained by applying the thermosetting resin composition (Z) of the present invention to various laminates and drying them by a known method. In addition, by attaching a release substrate to the adhesive layer after drying, it is possible to wind it up without causing offset to the substrate, which is excellent in operability, and since the adhesive layer is protected, it is excellent in storage properties and easy to use. In addition, if another release substrate is attached as necessary after applying and drying to the release substrate, it is possible to transfer the adhesive layer itself to another substrate.

[0068] <Release base material> Examples of the release substrate include a paper such as fine paper, craft paper, roll paper, or glassine paper, on both sides of which a coating layer of a filler such as clay, polyethylene, or polypropylene is provided, and a silicone-based, fluorine-based, or alkyd-based release agent is further applied on each coating layer. Other examples include various olefin films such as polyethylene, polypropylene, ethylene-α-olefin copolymer, and propylene-α-olefin copolymer alone, and films such as polyethylene terephthalate on which the release agent is applied. Due to the release force between the release substrate and the adhesive layer, and the adverse effect of silicone on electrical properties, it is preferable to use a polypropylene-sealed film on both sides of fine paper and an alkyd-based release agent thereon, or a polyethylene terephthalate film on which an alkyd-based release agent is applied.

[0069] In the present invention, examples of the method for coating the thermosetting resin composition (Z) on the substrate include a comma coater and a reverse roll coater. Alternatively, if necessary, the adhesive layer can be provided directly or by a transfer method on the rolled copper foil or polyimide film, which is a printed wiring board constituent material. The thickness of the adhesive layer after drying can be appropriately changed if necessary, but is preferably in the range of 5 to 200 μm. If the adhesive film thickness is less than 5 μm, the adhesive strength is insufficient. If it is 200 μm or more, there is a problem that drying is insufficient, the residual solvent increases, and blisters occur during pressing in the production of printed wiring boards. The drying conditions are not particularly limited, but the residual solvent rate after drying is preferably 1 wt % or less. If it exceeds 1 wt %, the residual solvent tends to foam during pressing of the printed wiring board, causing blisters.

[0070] <Printed wiring board> The "printed wiring board" in the present invention includes, as a component, a laminate formed from a metal foil and a resin substrate that form a conductor circuit. The printed wiring board is manufactured, for example, by a conventionally known method such as a subtractive method using a metal-clad laminate. If necessary, the printed wiring board is a general term for so-called flexible circuit boards (FPCs), flat cables, circuit boards for tape automated bonding (TAB), etc., in which a conductor circuit formed from a metal foil is partially or entirely covered with a cover film, screen printing ink, etc.

[0071] The printed wiring board of the present invention can be any laminated structure that can be used as a printed wiring board.For example, it can be a printed wiring board composed of four layers: a base film layer, a metal foil layer, an adhesive layer, and a cover film layer.Also, it can be a printed wiring board composed of five layers: a base film layer, an adhesive layer, a metal foil layer, an adhesive layer, and a cover film layer.

[0072] Furthermore, if necessary, two or more of the above printed wiring boards may be laminated.

[0073] The thermosetting resin composition (Z) of the present invention can be suitably used for each adhesive layer of a printed wiring board. In particular, when the thermosetting resin composition (Z) of the present invention is used as an adhesive, it has high adhesion not only to conventional polyimide, polyester film, and copper foil constituting a printed wiring board, but also to low-polarity resin substrates such as LCP, and can obtain solder reflow resistance, and the adhesive layer itself has excellent low dielectric properties. Therefore, it is suitable as an adhesive composition for use in coverlay films, laminates, resin-coated copper foils, and bonding sheets.

[0074] In the printed wiring board of the present invention, any resin film that has been conventionally used as a substrate for a printed wiring board can be used as the substrate film. Examples of the resin of the substrate film include polyester resin, polyamide resin, polyimide resin, polyamideimide resin, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resin, and fluorine resin. In particular, the substrate film has excellent adhesion to low polar substrates such as liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, and polyolefin resin.

[0075] <Cover film> As the cover film, any insulating film that is conventionally known as an insulating film for printed wiring boards can be used. For example, films made of various polymers such as polyimide, polyester, polyphenylene sulfide, polyethersulfone, polyetheretherketone, aramid, polycarbonate, polyarylate, polyimide, polyamideimide, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, and polyolefin resin can be used. More preferably, it is a polyimide film or a liquid crystal polymer film.

[0076] The printed wiring board of the present invention may be any conventionally known printed wiring board except for using the materials for each layer described above. The process can be used to manufacture the compound.

[0077] In a preferred embodiment, a semi-finished product is manufactured by laminating an adhesive layer on a cover film layer (hereinafter referred to as a "cover film side semi-finished product"). On the other hand, a semi-finished product is manufactured by laminating a metal foil layer on a base film layer to form a desired circuit pattern (hereinafter referred to as a "base film side two-layer semi-finished product"), or a semi-finished product is manufactured by laminating an adhesive layer on a base film layer and laminating a metal foil layer thereon to form a desired circuit pattern (hereinafter referred to as a "base film side three-layer semi-finished product") (hereinafter, the base film side two-layer semi-finished product and the base film side three-layer semi-finished product are collectively referred to as a "base film side semi-finished product"). By bonding the cover film side semi-finished product thus obtained and the base film side semi-finished product together, a four-layer or five-layer printed wiring board can be obtained.

[0078] The base film semi-finished product can be obtained, for example, by a manufacturing method including: (1) a step of applying a solution of a resin that will become the base film to the metal foil and initially drying the coating; and (2) a step of heat-treating and drying the laminate of the metal foil and the initially dried coating obtained in (1) (hereinafter referred to as the "heat treatment and desolvation step").

[0079] The formation of the circuit in the metal foil layer can be performed by a conventionally known method. Either an active method or a subtractive method can be used. The subtractive method is preferable.

[0080] The obtained semi-finished product on the base film side may be used as it is for bonding to the semi-finished product on the cover film side, or may be used for bonding to the semi-finished product on the cover film side after a release film has been bonded thereto and stored.

[0081] The cover film side semi-finished product is produced, for example, by applying an adhesive to the cover film. If necessary, a crosslinking reaction in the applied adhesive can be carried out. In a preferred embodiment, the adhesive layer is semi-cured.

[0082] The obtained semi-finished product on the cover film side may be used as it is for bonding to the semi-finished product on the substrate side, or may be used for bonding to the semi-finished product on the substrate film side after a release film has been bonded thereto and stored.

[0083] The substrate film-side semi-finished product and the cover film-side semi-finished product are stored, for example, in the form of a roll, and then laminated together to produce a printed wiring board. Any method can be used as a lamination method, and for example, they can be laminated together using a press or a roll. In addition, they can be laminated together while heating them by a method using a hot press or a hot roll device.

[0084] In the case of a reinforcing material that is soft and can be wound up, such as a polyimide film, the reinforcing material semi-finished product is preferably produced by applying an adhesive to the reinforcing material. In the case of a reinforcing plate that is hard and cannot be wound up, such as a metal plate such as SUS or aluminum, or a plate made of glass fiber cured with epoxy resin, the reinforcing material semi-finished product is preferably produced by transfer-coating an adhesive that has been applied in advance to a release substrate. If necessary, a crosslinking reaction can be carried out in the applied adhesive. In a preferred embodiment, the adhesive layer is semi-cured.

[0085] The obtained semi-finished product on the reinforcing material side may be used as it is for bonding to the rear surface of a printed wiring board, or may be used for bonding to a semi-finished product on the base film side after a release film has been attached and storage.

[0086] The base film side semi-finished product, the cover film side semi-finished product, and the reinforcing agent side semi-finished product are all laminates for printed wiring boards in the present invention.

[0087] <Cured product> The cured product of the present invention is a cured product obtained by curing the thermosetting composition (Z). That is, the cured product can be obtained by, for example, applying and casting the thermosetting composition (Z), removing the organic solvent (P) if necessary, and heating (preferably at 90 to 200°C, preferably for 1 minute to 6 hours). The shape of the cured product can be appropriately selected depending on the application, and examples of the shape include a coating film (preferably with a thickness of 5 to 1000 μm) and a cast product. EXAMPLES

[0088] The present invention will be further described below with reference to examples, but the present invention is not limited thereto. In the examples, the parts represent parts by weight. In the examples, the number average molecular weight (Mn), the number of double bonds of the polyolefin, the isotacticity, and the acid value were measured by the above-mentioned methods.

[0089] <Production Example 1> A reaction vessel was charged with 1,000 g of a high molecular weight polyolefin (A0-1) [trade name "Vistamaxx 6202", manufactured by Exxonmobil, the same applies below], and the liquid phase was heated and melted using a mantle heater while nitrogen was passed through it. The mixture was then thermally degraded at 380°C for 40 minutes while stirring, to obtain polyolefin (A-1). The polyolefin (A-1) had an Mn of 5,800, the number of double bonds at the molecular terminals and / or in the molecular chain per 1,000 carbons was 5.4, and the isotacticity was 18%.

[0090] <Production Examples 2 to 8, Comparative Production Examples 1 to 2> Polyolefins (A-2) to (A-8) and (Comparative A-1) to (Comparative A-2) were obtained by thermal degradation in the same manner as in Production Example 1, except that the high molecular weight polyolefin (A0), temperature, and time were changed according to Table 1. The results are shown in Table 1.

[0091] [Table 1]

[0092] <Production Example 11> 100 parts of polyolefin (A-1) and 2 parts of maleic anhydride (B-1) were charged into a reaction vessel, and after replacing with nitrogen, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly. A solution of 0.5 parts of a radical initiator [dicumyl peroxide, trade name "Percumyl D", manufactured by NOF Corp.] (C-1) dissolved in 5 parts of xylene was added dropwise thereto over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Thereafter, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa, the same applies below) to obtain an acid-modified polyolefin (X-1). The acid-modified polyolefin (X-1) had an acid value of 11, Mn of 7,000, and isotacticity of 16%.

[0093] <Production Example 12> 100 parts of polyolefin (A-1) and 3 parts of maleic anhydride (B-1) were charged into a reaction vessel, and the mixture was heated to 200°C under nitrogen aeration and stirred for 10 hours. After that, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa, the same applies below) to obtain an acid-modified polyolefin (X-2). The acid-modified polyolefin (X-2) had an acid value of 16, Mn of 6,000, and isotacticity of 18%.

[0094] <Production Examples 13 to 23, Comparative Production Examples 11 to 12> Except for using the raw materials according to Table 2, the reaction was carried out in the same manner as in Production Example 11 to obtain each acid-modified polyolefin (X). The results for each of the resulting acid-modified polyolefins (X) are shown in Table 2.

[0095] [Table 2]

[0096] <Example 1> In a 500 ml four-neck flask equipped with a water-cooled reflux condenser and a stirrer, 100 parts of acid-modified polyolefin (X-1), 224 parts of methylcyclohexane, and 96 parts of methyl ethyl ketone were charged, heated to 80°C with stirring, and dissolved by continuing stirring for 1 hour. 10 parts of epoxy resin (Y-1) [YDCN-700-10] was added to the solution obtained by cooling to 50°C to obtain a thermosetting composition (Z-1).

[0097] <Examples 2 to 23, Comparative Examples 1 to 2> Each thermosetting resin composition (Z) was obtained in the same manner as in Example 1, except for following Table 3. The pot life, adhesive strength, solder heat resistance, and electrical properties (frequency 1 MHz) of each obtained thermosetting resin composition (Z) were evaluated, and the results are shown in Table 1.

[0098] (1) Pot life It refers to the stability of the solution 24 hours after mixing at 23°C. When the pot life is good, it means that there is little increase in the viscosity of the solution and it can be stored for a long time, and when the pot life is poor, the viscosity of the solution increases (thickens) and, in severe cases, gelation occurs, making it difficult to apply to a substrate and making it impossible to store for a long time. <Evaluation criteria> ◎: Can be applied ○: Viscosity increases and processability is poor, but coating is possible △: Viscosity increase or gelation makes application difficult ×: No fluidity, cannot be applied

[0099] (2) Peel strength (adhesive strength) The thermosetting resin composition (Z) was applied to a polyimide film (Apical, manufactured by Kaneka Corporation) having a thickness of 25 μm so that the thickness after drying would be 25 μm, and then dried at 130° C. for 3 minutes. The adhesive film (B stage product) thus obtained was laminated to 18 μm rolled copper foil. The lamination was performed at 160° C. and 40 kgf / cm with the shiny side of the rolled copper foil in contact with the adhesive. 2 The pieces were pressed for 30 seconds under a pressure of 1000 psi to bond them together. The film was then heat treated at 140°C for 4 hours to harden it, and a sample for evaluating peel strength was obtained. The peel strength was measured by a 90° peel test at 25°C, with the film pulled at a tensile speed of 50mm / min. This test indicates the adhesive strength at room temperature.

[0100] <Evaluation criteria> ◎:1.5N / mm or more ○: 1.0N / mm or more and less than 1.5N / mm △: 0.8N / mm or more and less than 1.0N / mm ×: Less than 0.8N / mm

[0101] (3) Solder heat resistance (heat resistance) Samples were prepared in the same manner as in (2) above, and 2.5 cm x 2.5 cm sample pieces were dried at 120°C for 30 minutes. They were then allowed to flow in a molten solder bath at each temperature for 1 minute, and the temperature at which no changes in appearance, such as swelling, occurred was measured.

[0102] <Evaluation criteria> ◎: 300℃ or higher ○: 290℃ or higher and less than 300℃ △: 270℃ or higher but less than 290℃ ×: Less than 270℃

[0103] (4) Dielectric constant (ε) and dielectric tangent (tan δ) [Electrical properties] The thermosetting resin composition (Z) was applied to a release film having a thickness of 50 μm so that the thickness after drying would be 30 μm, and then dried at 130° C. for 3 minutes. The film was then cured by heat treatment at 140°C for 4 hours, and then peeled off from the release film and measured. Measurements were performed using a PRECISION LCR meter HP-4284A at 22°C, 58% RH, and a frequency of 1 MHz, and the results were evaluated as follows. Similarly, measurements were performed using a VECTOR NETWORK ANALYZER HP8510C, a SYNTHESIZED SWEEPER HP83651A, and a TESTSET HP8517B at 22°C, 58% RH, and a frequency of 1 GHz, and the results were evaluated as follows.

[0104] <Evaluation criteria for dielectric constant> ◎: 2.3 or less ○: More than 2.3 and 2.6 or less △: More than 2.6 and less than 3.0 ×:Over 3.0 <Evaluation criteria for dielectric tangent> ◎: 0.005 or less ○: More than 0.005 and 0.01 or less △: More than 0.01 and less than 0.02 ×: More than 0.02

[0105] [Table 3]

[0106] In Table 3, the ingredients are as follows: (Y-1): o-cresol novolac type epoxy resin [YDCN-700-10, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.] (Y-2): Bisphenol A type epoxy resin [JER-828, manufactured by Mitsubishi Chemical Corporation] (Y-3): Dicyclopentadiene type epoxy resin [HP-7200, manufactured by DIC Corporation] (Y-4): Naphthalene type epoxy resin: [HP-4700, manufactured by DIC Corporation] (P-1): Methylcyclohexanone (P-2): Methyl ethyl ketone (P-3): Toluene (P-4): Cyclohexane

[0107] From the results in Tables 1 to 3, it can be seen that the thermosetting resin composition (Z) of the present invention has a superior pot life and adhesive strength as compared with the comparative compositions, and the cured product has superior heat resistance and electrical properties. [Industrial Applicability]

[0108] The thermosetting resin composition (Z) of the present invention has excellent pot life and adhesive strength. In addition, the cured product has excellent heat resistance and electrical properties (low dielectric properties) [dielectric constant, dielectric loss tangent]. Therefore, it can be used for various purposes, but is preferably used for adhesion, and more preferably for adhesion between a resin substrate and a resin substrate or a metal substrate.

Claims

1. A thermosetting resin composition (Z) comprising an acid-modified polyolefin (X) and an epoxy resin (Y), wherein the acid-modified polyolefin (X) comprises a polyolefin (A) and an unsaturated carboxylic acid (B) as constituent raw materials, the weight ratio of ethylene, which is a constituent monomer of the polyolefin (A), to an α-olefin having 3 to 8 carbon atoms [ethylene / α-olefin having 3 to 8 carbon atoms] being 2 / 98 to 50 / 50, the unsaturated carboxylic acid (B) being an unsaturated monocarboxylic acid, an unsaturated polycarboxylic acid, and / or an unsaturated polycarboxylic anhydride, and the acid-modified polyolefin (X) satisfies all of the following requirements (1) to (3): (1) Acid value is 1 to 100 mgKOH / g (2) Number average molecular weight (Mn) of 1,000 to 60,000 (3) Isotacticity of the α-olefin portion is 1 to 50%

2. 2. The thermosetting resin composition according to claim 1, wherein the polyolefin (A) has a number average molecular weight of 800 to 50,000.

3. 3. The thermosetting resin composition according to claim 1, wherein the polyolefin (A) has 0.5 to 20 double bonds per 1,000 carbon atoms.

4. The epoxy resin (Y) is mixed with 5 to 100 parts by weight of the acid-modified polyolefin (X). The thermosetting resin composition according to any one of claims 1 to 3, comprising 1000 parts by weight of the thermosetting resin composition.

5. 5. The thermosetting resin composition according to claim 1, further comprising 10 to 1000 parts by weight of an organic solvent (P) based on 100 parts by weight of the acid-modified polyolefin (X).

6. The thermosetting resin composition according to any one of claims 1 to 5, which is used for bonding a resin substrate to another resin substrate or a metal substrate.

7. A laminate comprising a resin substrate bonded with the thermosetting resin composition (Z) according to any one of claims 1 to 6, and a resin substrate or a metal substrate.

8. An adhesive sheet comprising the laminate according to claim 7 .

9. A printed wiring board comprising the laminate according to claim 7 or the adhesive sheet according to claim 8 as a component.

10. A cured product obtained by curing the thermosetting composition (Z) according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Propylene copolymer, composition and adhesive comprising the same

    JP2004067729A

  • Modified polypropylene and modified polypropylene composition

    JP2005187532A

  • Adhesive, and cover-lay for flexible printed circuit board

    JP2007063306A

  • Modified polyamide resin and resin composition containing the same

    JP2007284515A

  • Polyolefin-based graft copolymer and adhesive composition

    JP2009221328A